Predictors of Resilience Among Adolescent Girls and Young Women Who Have Experienced Intimate Partner Violence and Sexual Violence in South Africa - Kuo, Caroline (Journal of interpersonal violence, 2022)
South Africa has some of the highest rates of intimate partner and sexual violence globally, with prevalence ranging from 10% to 21% among adolescent girls and young women (AGYW). Yet, few studies characterize the relationship between violence and resilience. Identifying factors associated with resilience following exposure to violence can guide the development of strength-based interventions that change modifiable protective factors to bolster resilience. Data were derived from a cross-sectional survey of AGYW aged 15 to 24 years in South Africa that took place from 2017 to 2018. This survey was part of a national evaluation of a South African combination HIV intervention for AGYW funded by the Global Fund to Fight AIDS, TB, and Malaria. A sample of 4,399 observations was achieved through a systematic random sampling frame of 35% of households in districts where AGYW were at highest risk for HIV, and where the intervention was implemented. Resilience was assessed using the Connor-Davidson Resilience Scale. Intimate partner and sexual violence were assessed using: (a) an adapted version of a questionnaire from the World Health Organization?s 2005 multicountry study on domestic violence against women, and (b) questions on lifetime experience of forced sex/rape. Nearly a third of AGYW (29.6%) reported intimate partner emotional and/or physical and/or sexual violence in the past year. Nearly a quarter of AGYW (23.74%) reported emotional violence, 17.48% reported physical violence, and 6.37% reported sexual violence from intimate partners. Nearly 8% (7.72%) reported forced sex/rape from intimate partners and/or nonpartners. More equitable gender norms, higher social support, and hazardous drinking were positively associated with higher resilience among those who experienced physical or sexual violence. This study addresses a gap in the resilience and violence literature. Future research should focus on the development of resilience-promoting interventions for individuals who have experienced violence.